Pivot or die : how leaders thrive when everything changes - Shapiro, Gary (New York, NY : William Morrow, an imprint of HarperCollins Publisher, 2024)
"From Gary Shapiro, New York Times bestselling author and head of CES and the Consumer Technology Association, a manifesto for today's top executives, entrepreneurs, and leaders: pivot or die"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Leadership; Entrepreneurship; Businesspeople